A coupled adhesive-frictional model tailored for interfacial behaviors between UHPC and NC materials. (April 2022) - Yuan, Siqi; Liu, Zhao; Tong, Teng; Wang, Yangchun
Highlights: The interfacial behaviors between UHPC and NC materials are realistically captured by the proposed adhesive-frictional model. Zero-thickness cohesive element is adopted to implement the model within implicit finite element solver. The model is validated through several experiments reported in literatures. Abstract: In this paper, a coupled adhesive-frictional is proposed and implemented within an implicit finite element (FE) solver, targeting interfacial behaviors between ultrahigh-performance concrete (UHPC) and normal concrete (NC) materials. The model couples the adhesive force and frictional force, which is consistent with the mainstream shear-friction theory. The proposed model is realized by the zero-thickness cohesive element, thorough user-defined element (UEL) subroutine provided by the general FE software Abaqus/Standard . The model satisfactorily predicts the bond strength between UHPC and NC materials subject to various statuses, i.e., the tensile force (direct-tensile test), and combined compressive and shear forces (slant shear test). In addition, the interfacial model works fully compatible with the concrete damaged plasticity model, which is adopted for the UHPC and NC materials. The combination of these two models yields agreed with simulation results, which effectively predicts various cracking propagation and failure patterns of UHPC-NC composite specimens. The specimens in literatures are selected for comparisons and the numerical simulations clearly illustrate the complex interactions between the matrix cracking and interfacial debonding.